Peran Guru Dalam Pengembangan Kurikulum Berbasis Nilai Islam Di Smp Nurul Islam Ngemplak - Windy Lestari; Syafina Aulia Nisa; An Nisa Jihan Nur Fitri Aini; Linda Rizki Oktaviani; Siti Khumairoh; Praptiningsih . (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research wants to describe how teachers play a role in developing a curriculum based on Islamic values at Nurul Islam Ngemplak Boyolali Junior High School. In addition, the research also highlights the efforts made by teachers and the challenges they face in the process. The method used is qualitative descriptive with a field research approach. Data was collected through observation, interviews, and documentation, with curriculum teachers and Islamic Religious Education (PAI) teachers as the main informants. The results of the study show that teachers have an important role, not only as a compiler of learning plans, but also as planners, implementers, evaluators, as well as curriculum developers. They do not only make lesson plans, but also try to incorporate Islamic values into every teaching and learning activity. In addition, teachers try to adapt the curriculum to the characteristics of students through a contextual approach and habituation of Islamic values in the school environment. The challenges faced include rapid changes in curriculum policies, limited training, and the need to adapt to modern learning concepts such as differentiation and Pancasila student profile projects. Nevertheless, teachers remain committed to improving their competencies through independent learning and collaboration between peers. Thus, the development of an Islamic value-based curriculum at Nurul Islam Junior High School is dynamic and oriented towards the formation of Islamic character that is in line with the school's vision.